Expression profiling of HSP 70 and interleukins 2, 6 and 12 genes of Barki sheep during summer and winter seasons in two different locations - Raed A. Abu Rawash; Mahmoud A. Sharaby; Gamal El-Din A. Hassan; Alaa E. Elkomy; Elsayed E. Hafez; Salma H. Abu Hafsa; Mohamed M. I. Salem (International Journal of Biometeorology, 2022)
The objectives of this research were to contrast the expression values of heat shock protein (HSP70) and interleukins 2, 6 and 12 (IL 2, IL 6 and IL 12) genes in summer and winter in two different locations in Egypt (Alexandria zone and Matrouh zone) to deduce changes in thermo-physiological traits and biochemical blood metabolites of Barki sheep. A total of 50 ewes (20 in Alexandria and 30 in Matrouh) were individually blood sampled to determine plasma total protein (TP), Albumin, Globulin and Glucose constituents and T3, T4 and cortisol hormones. The thermo-physiological parameters of rectal temperature (RT, °C), skin temperature (ST, °C), Wool temperature (WT, °C), respiration rate (RR, breaths/min) and pulse rate (PR, beats/min) were measured for each ewe. Expressions of IL 2, IL 6, IL 12 and HSP 70 in summer and winter were analyzed along with thermo-physiological parameters and blood biochemical metabolites. In both locations, THI had significant effects on ST, WT, PR and RR, but not significant on RT. However, it had no significant effects on blood plasma metabolites and hormonal concentrations in the two locations in summer and winter. In Alexandria location, THI had negative significant effect on the expressions of IL-2 and IL-6 but positively affected on HSP70 genes in winter, while the expression of IL-12 gene was not affected by seasons, whereas in Matrouh zone, the effects of THI on the expressions of all tolerance genes were not significant. The results of the current study suggest that IL-2, IL-6 and HSP70 genes could be used as molecular markers for heat/cold stress.